Features of the impact of psychoemotional burnout on the deformation of the self-concept of a deprived personality: a theoretical perspective on the problem - Hoshovska, Daria; Hoshovskyi, Yaroslav; Rudnytskyi, Oleksandr (Psychological Prospects Journal, 2023)
Purpose. To establish the features of the impact of psychoemotional burnout on the deformation of the self-concept of a deprived personality. Methods. To achieve the research objective, we employed a system of scientific and theoretical methods, including analysis, synthesis, abstraction, and generalization, which allowed us to establish the phenomenology of the negative impact of psychoemotional burnout on the construction/reconstruction of the self-concept of a person whose life is characterized by deprivation. Results. The analytical review of the scientific-psychological sources allowed us to assert that psychoemotional burnout generally has a negative impact on the psycho- and sociogenesis of a deprived personality, primarily on its self-awareness and construction of its own self-concept. Psychoemotional burnout unfolds in the spatial-temporal dimensions of the activity and communication of a deprived person and leads to the emergence of psychological (affective, intellectual, motivational, behavioral, etc.) disorders as well as significant psychosomatic changes. In conditions of deprivation, there is usually a disproportion between the system of constructed self-representations and the way in which the personality would like to be (the dichotomy of "real-self" and "ideal-self"). Psychoemotional burnout results in the construction of the self-concept being complex and ambiguous, and acquiring characteristics of chaos, diffuseness, imbalances, and so on. Conclusions. The regime of various types of deprivation has a negative impact on personality development, hinders optimistic trajectories of growth, blocks the effectiveness of interpersonal communication, suppresses emotional-volitional efforts and manifestations, cultivates insecurity, indecisiveness, social pessimism and leads to the appearance of usually depressive modes of self-awareness. Burnout also causes psychophysical fatigue, passivity, significant impoverishment of the content of the worldview and deformation of self-awareness. As a result, there are problems with creating adequate self-esteem, a system of self-images, and a harmonious self-concept of personality.